GENERATING RESPONSES IMMUNE IN CELLULAR AND HUMORAL TREATMENT WITH EPITOPE SPIKE, EPITOPE ENVELOPE PROTEIN, AND EPITOPE MEMBRANE PROTEIN SARS-COV-2, HONEY, SAUSSUREA LAPPA, AND NIGELLA SATIVA - Prawiro, Sumarno Reto; Kusuma, Meike Tiya; Amiruddin, Reyhan; Sukmawati, Irma Nur; Kusnaningrum, Yuyun; Davi S Nadarajah, Jayshri; Anam, Khoirul; Mardining Raras, Tri Yudani; Winarsih, Sri (African Journal of Infectious Diseases (AJID), 2021)
Background: Covid-19 has become pandemic in the world, including Indonesia. Our last study showed that HSF can serve as an immunomodulator. Using the exact search, we found that the most immuno-dominant SARS-COV2 epitope, namely A spike protein epitope, B envelope protein epitope, and C membrane protein epitope, we concise to be HF Materials and Methods: We used post only control design study and mice as an animal model. The research divided mice into four groups, and the first group as control received PBS as a placebo. The second, three, and last four groups gave HF, HSN, and HFHSN (combine HF and HSN). All of the regiment enters the mouth with a special sonde to reach the gastrointestinal organ. We gave HF every week three times and HSN once a day. After administration regiments for a long three weeks, we sacrificed the mice. We evaluated cellular immune responses that are Th-2, Th-17, and NK cells. We check for humoral immune response, TGF-β, IL-17A, IL-4, IgG, IL-4, β-defensin, and s-IgA. Results: Highest profile cellular immunity HF, HSN, and HFHSN were NK cell, Th-2 and Th-17, and the last NK cell, respectively. After that which in humoral immunity, the domination response IgG and IL-4 were HF. But HSN and HFHSN dominated for s-IgA and β-defensin production. By using study Bio-Informatica, we found HF. Conclusion: If the results of this study are continued to the clinical trial level, it is necessary to recommend additional markers such as CTL (s-IgA and β-defensin in lung tissue)